Pelatihan Mobile Braille Touch (MBT) pada Peserta Didik Upt Tunanetra Jawa Timur - Anik Nur Handayani; Heru Herwanto; Wahyu Irianto; Achmad Safi’i (Universitas Ngeri Malang, 2021)
MBT (Mobile Braille Touch) is a specific mobile phone application for people with disabilities, particularly those who are blind. The ADDIE research paradigm was utilized in the development of the MBT application, which includes the stages of Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation. The result is an MBT learning media application with audio and visual output that is more easily comprehended by those with visual impairments because of its development. With the help of e-braille, blind persons can learn, practice, write, translate, aid, regulate, and speed up their writing. The goal of this service is to teach persons with disabilities, especially the visually impaired, how to use mobile phones to aid in the learning process and communicate with one another using the MBT (Mobile Braille Touch) application. The conclusion of this service is that people with impairments, particularly the visually impaired, can comprehend and use mobile phones in the learning process without limitations (place and time) and with ease. MBT (Mobile Braille Touch) merupakan suatu aplikasi mobile phone khusus yang digunakan untuk penyandang disabilitas khususnya tunanetra. Pengembangan yang digunakan dalam pembuatan aplikasi MBT yaitu model penelitian ADDIE dengan tahapan Analysis, Desaign, Development or Production, Implementation or Delivery, dan Evaluation. Berdasarkan pengembangannya, produk yang dihasilkan yaitu aplikasi media belajar MBT yang memiliki keluaran berupa audio dan visual sehingga bisa lebih mudah dimengerti oleh penyandang tunatera. Adapun fitur yang ada pada e-braille ini memungkinkan penyandang tunanetra dapat belajar, latihan, menulis, terjemah, bantuan, pengaturan hingga kecepatan menulis menggunakan mobile phone. Tujuan pengabdian ini ialah untuk melatih aplikasi MBT (Mobile Braille Touch) kepada penyandang disabilitas khususnya tunanetra dalam penggunaan mobile phone khusus untuk membatu dalam proses pembelajaran serta berkomunikasi antar sesama. Adapun kesimpulan dari pengabdian ini yaitu penyandang disabilitas khususnya tunanetra dapat memahami dan menggunakan mobile phone dalam proses pembelajaran tanpa batas (ruang dan waktu) serta kemudahan dalam berkomunikasi.